Nutritional contribution of breakfasts selling in public roads - Marquina-Ruiz, Giovanna (2024)
A descriptive, quantitative and cross- sectional research about the nutritional contribution and % nutritional adequacy of energy, macronutrients, micronutrients, dietary fiber, added sugar and energy density of some types of food and beverages most consumed for breakfasts (quinoa drink, oatmeal drink, maca drink, avocado sandwich, chicken sandwich and bread with vegetable fritters) selling in public roads in Lima. The breakfast most demanded by women (a drink accompanied by a sandwich) covered 80,6 % of their energy recommendations, 77.1 % of proteins, 88,3 % of total fat, 72.7 % of total carbohydrates, 12,8 % calcium, 102.4 % iron, 7.6 % vitamin A, 29.4 % vitamin C, 272.3 % added sugar, 25.1 % saturated fat and 33 % dietary fiber. Regarding the nutritional contribution of breakfast preferred by men (a drink accompanied by two sandwiches), it contributed to 76.4 % of energy recommendations, 59.8 % of proteins, 76.9 % of total fat, 81.8 % of total carbohydrates, 36.7 % of calcium, 311.9 % of iron, 49.8 % of vitamin A, 59.4 % of vitamin C, 184.3 % of added sugars and 56.9 % of dietary fiber. The results revealed excessive amounts of added sugars, and deficiencies in energy, protein, carbohydrates, dietary fiber and micronutrients intakes. In addition, the energy density of these drinks and the avocado sandwich was low (0.4 kcal/g and 1.8 kcal/g, correspondingly), meanwhile the energy density of the chicken sandwich was the highest (3.6 kcal/g).